Intervención urbano arquitectónica en la plaza del mercado Simón Bolívar y su área de influencia comercial en el barrio San Alfonso – Riobamba - Cuadrado Avilés, Christian Ricardo (2025)
The project is aimed at the urban-architectural intervention of the Simón Bolívar Market Square located in the San Alfonso neighborhood of the Riobamba Canton. The current problem includes traffic disorder, human mobility, and the overflow of informal merchants on nearby roads. For the study, bibliographic and field research has been carried out to gather information, macro and micro diagnosis, and experimental research for the urban- architectural proposal of the market and its surroundings. Among the most important results are two days with greater flow on Wednesdays and Saturdays, which are fairs throughout the city, which generates conflict points that are concentrated explicitly on Junín and five de Junín streets and disorder. There is also a lack of sanitation inside and around the market. Strategies and a proposal are proposed that include the specialization of markets in the city, underground parking and restructuring of roads to accommodate social activities, internal reorganization of the market specialized in fruits, vegetables, and legumes, increasing the number of stalls by 50% to welcome new merchants of the products mentioned above, in the same way, two lateral strips of public space are opened in direct relationship with the heritage environment.